Identify Factors Associated with Scabies Aged 6-19 Years Old in The Boarding School - Zata Ismah; Reinpal Fahlepi; Dinda Asa Ayukhaliza; Cindy Lestari; Siti Maisyaroh Siregar (Universitas Teuku Umar, 2021)
Scabies is a significant worldwide health problem in boarding school children with dangerous systemic complications and an increased risk of mortality because of low priority for treatment. The method uses systematic review. Data sources were collected from databases such as Pubmed and Google Scholar regarding the incidence of scabies in boarding schools indexed nationally and internationally in 2014 - 2019. The exhaustive literature obtained is 15 studies, totaling 2490 samples by determining the required variables. Data analysis was performed by looking at OR, RR, and PR. The significant risk factors for school scabies were age, gender, personal hygiene, room conditions (Room humidity, ventilation, lighting), contact history, occupancy density, risky habits (Sharing a bed, clean clothes, exchanging personal items). The highest risk factor for the incidence of scabies was occupancy density (OR = 24,200, 95% CI = 7,990 - 73,299). Second is the room conditions (OR = 15,000, 95% CI = 3,639 - 61,832); third is personal hygiene (OR = 13,714, 95% CI = 4,210 - 44,677). The intervention will effectively reduce risk factors that contribute to scabies, namely occupancy density, room conditions, and personal hygiene. The ratio of the number of students in a room, room conditions are highly recommended to meet health requirements. Then the improvement of personal hygiene behavior for every occupant of the school. This is to reduce the high rate of spread of scabies infection, especially in boarding-based schools.